2011
DOI: 10.1016/j.jacc.2011.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Collagen Deposition in Infarcted Myocardium Facilitates Induced Pluripotent Stem Cell Engraftment and Angiomyogenesis for Improvement of Left Ventricular Function

Abstract: Objectives The purpose of this study was to assess the effect of scar tissue composition on engraftment of progenitor cells into infarcted myocardium. Background Scar tissue formation after myocardial infarction creates a barrier that severely compromises tissue regeneration, limiting potential functional recovery. Methods In vitro: A tricell patch (Tri-P) was created from peritoneum seeded and cultured with induced pluripotent stem cell–derived cardiomyocytes, endothelial cells, and mouse embryonic fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 20 publications
(28 reference statements)
3
65
0
Order By: Relevance
“…A cardiac tissue sheet reassembled with defined cardiovascular populations (including purified hiPSC-derived cardiomyocytes and New Journal of Science ECs) was implanted in an animal MI model which showed significant and sustained improvement of cardiac function accompanied by neovascularization [193,194]. In our studies, a tricell omentum patch (seeded with iPSC-derived cardiomyocytes, ECs, and MEFs) was created and implanted into mice resulting in significantly higher cell engraftment accompanied by angiomyogenesis in the infarcted area and improvement in heart function [195,196]. The combination of cell sheet and the omentum flap has emerged as a promising iPSC technique for the development of tissue-engineered vascular-rich new myocardium in vivo [197].…”
Section: Cardiovascular Differentiationsmentioning
confidence: 98%
See 1 more Smart Citation
“…A cardiac tissue sheet reassembled with defined cardiovascular populations (including purified hiPSC-derived cardiomyocytes and New Journal of Science ECs) was implanted in an animal MI model which showed significant and sustained improvement of cardiac function accompanied by neovascularization [193,194]. In our studies, a tricell omentum patch (seeded with iPSC-derived cardiomyocytes, ECs, and MEFs) was created and implanted into mice resulting in significantly higher cell engraftment accompanied by angiomyogenesis in the infarcted area and improvement in heart function [195,196]. The combination of cell sheet and the omentum flap has emerged as a promising iPSC technique for the development of tissue-engineered vascular-rich new myocardium in vivo [197].…”
Section: Cardiovascular Differentiationsmentioning
confidence: 98%
“…This problem can be improved by morphological selection, label or staining strategies using fluorescence activated cell sorters (FACS), and drug selection approaches [247][248][249]. For instance, after defined differentiation induction of iPSCs, our previous studies used FACS to isolated CD31 positive derived ECs and purified NCX1 positive derived cardiomyocytes by puromycin resistance selection [195,196]. NKX2-5 positive cardiomyocytes from iPSCs were purified by FACS and survived upon transplantation into the infarcted mouse heart without formation of teratomas [250].…”
Section: Safety Issuesmentioning
confidence: 99%
“…Recent studies have shown that induced pluripotent stem cells (iPSC) may have therapeutic potential (13). Experimental studies in animals have yielded encouraging results when iPSC are transplanted into peri-infarction myocardial zones (4). Treatments with iPSC appear to result in an improvement in cardiac contractile function (4), but numerous questions remain unanswered with regard to the use of such cells as therapy for post-MI repair.…”
mentioning
confidence: 99%
“…It has been confirmed that PCs secrete cytokines, chemokines, and growth factors that could potentially promote repair of injured cardiac tissue (10). Two mechanisms have been suggested by which cardiac repair after an ischemic insult can occur: (i) PC differentiation directed toward a coordinated generation of new cardiac muscle cells and accompanying establishment of a new or expanded microcirculation (7) and (ii) PC secretions of paracrine factors, including cytokines, chemokines, and growth factors that alone or in combination recruit new reparative cells to the injury area and promote and support in situ tissue repair process (4,7,10,13). The latter paracrine mechanism could potentially provide for a noncell-based alternative to the PC use in treatment of cardiovascular disease (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation